Evaluating the Concentrations of Toxic and Carcinogenic Elements in the Soil of Basra Governorate and the Extent of their Impact on the Spread of Some Diseases - Ali Nasser Abdullah Al-Sarayfi ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
A comprehensive survey of the soil was conducted in Basra Governorate by studying the heavy elements that affect the environment, especially the radioactive elements. Soil samples with a depth ranging between (5-20) cm were taken from five districts (Quanah, Shatt al-Arab, Al-Faw, Al-Zubair, Basra. According to the seasons of the year 2020, through which (38) toxic elements were studied, in addition to studying some of the chemical properties of the soil to find out the relationship between the studied elements and chemical properties, and the results of the study showed the high concentration of heavy elements in the districts (Qurnah, Shatt al-Arab, Al-Faw) compared With the districts of